Komunikasi Sebagai Strategi Bisnis dalam Meningkatkan Loyalitas Pelangga pada Konter Paket Data Internet Kecamatan Peterongan Jombang - Muchammad Nur Andie Setyawan (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
This research aims to find out how important it is to interact with buyers at internet data package counters which can support an effort to increase customer loyalty. Customer loyalty is defined as people who buy, especially those who buy regularly and repeatedly. In this research, the impact of brand image and consumer satisfaction on customer loyalty has a very significant influence on consumer satisfaction. In achieving this goal, this research uses descriptive qualitative research methods with data collection techniques through interviews, observation, documentation and literature review. The location of this research is at the internet data package counter in Peterongan District, Jombang Regency, which focuses on three internet data package counters, namely Alvers Cell, Ica Cell, and Ara cell. The results of this research show that the strategy for increasing customer loyalty carried out by internet data sellers is to invite customers to communicate well and appropriately. Customer loyalty today is not only driven by need, but a service system that builds good communication will be a consideration for consumers to be loyal.